СУЩЕСТВУЕТ ЛИ МЕЙНСТРИМ В ЛИНГВИСТИКЕ – II?1 (Филологические заметки, 2019)
This article is the continuation of the text published in one of the previous issues of Philological notes. The problem of the status of modern linguistics is discussed in the form of an antique dialogue. Besides, the author’s understanding of some linguistic terms which have not been correspondingly defined in the previous article is specified there by the author.